Wetting characteristics of spodumene surfaces as influenced by collector adsorption. (January 2019) - Zhu, Guangli; Wang, Xuming; Li, Enze; Wang, Yuhua; Miller, Jan D.
Highlights: Spodumene surfaces are naturally hydrophilic. Interfacial water structure is described for each surface. Surface state accounts for collector adsorption. Oleate chemisorbs at aluminum sites for the (1 0 0) and (1 1 0) surfaces. Dodecyl amine adsorbs at all surfaces. Abstract: The selective flotation separation of spodumene from other aluminosilicate minerals remains a challenging problem in flotation chemistry, and the surface chemistry features are of fundamental importance. In this study, the interfacial chemistry features, particularly the wetting characteristics of selected spodumene surfaces (1 1 0, 0 0 1, 0 1 0, and 1 0 0 crystal surfaces), in the absence and presence of collectors, were studied by water contact angle and bubble attachment measurements, molecular dynamics (MD) simulation, and sum-frequency vibrational spectroscopy (SFVS). The experimental results revealed the interfacial water structure at spodumene surfaces. Contact angle, bubble attachment measurements, and MD simulation results showed that the four spodumene surfaces were naturally hydrophilic, whereas in the presence of collectors, preferential adsorption of sodium oleate on the (1 0 0) and (1 1 0) surfaces was found to create a hydrophobic surface state. Detailed analysis of the interfacial water structure was conducted in order to understand the wetting characteristics at the molecular level, and SFVS was used to study the state of collectors at selected surfaces. The MD simulation and SFVS results revealed that the natural state of the surfaces contributes to the distinct interfacial water structure and the adsorption state of collectors. It seems that unsaturated Al sites at the spodumene surface and their spatial locations account for chemisorption of sodium oleate, while electrostatic attraction appears to be the main driving force for dodecylamine adsorption.